Spatial relations among environmental factors and phlebotomine sand fly populations (Diptera: Psychodidae) in central and southern Morocco. Issue 2 (December 2015) - Kahime, K.; Boussaa, S.; El Mzabi, A.; Boumezzough, A.
ABSTRACT: Phlebotomine sand flies (Diptera: Psychodidae, Phlebotominae) are of considerable public health importance because of their ability to transmit several human parasites, mainly as vectors of Leishmania spp. Over the past decade, the epidemiological situation of cutaneous leishmaniasis (CL) has significantly increased with its geographic expansion to previously free areas and the emergence of overlapping foci of cutaneous leishmaniasis and visceral leishmaniasis (VL) in several provinces of Morocco. A total of 15, 313 specimens was collected during this entomological survey. The genera Phlebotomus (57.38%) and Sergentomyia (42.62%) were identified. Sergentomyia minuta (22.01%) was the most prevalent species, followed by S. fallax (18.21%), Phlebotomus perniciosus (14.35%), P. papatasi (14.06%), P. sergenti (12.85%), P. longicuspis (10.74%), P. ariasi (2.68%), S. dreyfussi (1.53%), P. alexandri (1.31%), P. bergeroti (1.14%), S. christophersi (0.62%), S. africana (0.25%), P. chabaudi (0.14%), P. chadlii (0.05%), and P. kazeruni (0.04%). We aimed to determine current distribution of leishmaniases vectors, their ecological characteristics, and the significance of the predominant species at any bioclimate stage, altitude range, and soil texture in terms of the risk of leishmaniasis transmission.